2015
DOI: 10.1002/ange.201502763
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras Signaling by Blocking Ras–Effector Interactions with Cyclic Peptides

Abstract: Ras genes are frequently activated in human cancers, but the mutant Ras proteins remain largely "undruggable" by the conventional small-molecule approach due to absence of any obvious binding pockets on their surfaces. By screening a combinatorial peptide library followed by structure-activity relationship analysis, we discovered a family of cyclic peptides possessing both Ras-binding and cell-penetrating properties. These cell-permeable cyclic peptides inhibited Ras signaling by binding to Ras-GTP and blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 36 publications
(39 reference statements)
1
59
0
3
Order By: Relevance
“…15,16 Recent examples demonstrate the potential of macrocyclic peptides as inhibitors of small GTPase PPIs. [17][18][19][20][21] In this context, we reported hydrocarbon stapled peptides as the first direct modulators of a Rab GTPase in its activated GppNHp-bound form. 4,14 The peptide StRIP3 represents the best-characterized derivative, which binds Rab8a(GppNHp) with moderate affinity and is able to inhibit a Rab8a PPI in vitro.…”
Section: Introductionmentioning
confidence: 97%
“…15,16 Recent examples demonstrate the potential of macrocyclic peptides as inhibitors of small GTPase PPIs. [17][18][19][20][21] In this context, we reported hydrocarbon stapled peptides as the first direct modulators of a Rab GTPase in its activated GppNHp-bound form. 4,14 The peptide StRIP3 represents the best-characterized derivative, which binds Rab8a(GppNHp) with moderate affinity and is able to inhibit a Rab8a PPI in vitro.…”
Section: Introductionmentioning
confidence: 97%
“…[31,32] Building on their previous work showing that cyclic peptides could efficiently disrupt the interaction between Ras and its effectors, [32] Upadhyaya et al recently reported improved constructs possessing high cell permeability. [31,32] Building on their previous work showing that cyclic peptides could efficiently disrupt the interaction between Ras and its effectors, [32] Upadhyaya et al recently reported improved constructs possessing high cell permeability.…”
Section: Cyclic Peptidesmentioning
confidence: 99%
“…[31,32] Aufbauend auf ihren früheren Arbeiten, in denen sie das effiziente Aufbrechen von Wechselwirkungen zwischen Ras und seinen Effektoren mithilfe kleiner Peptide demonstriert hatten, [32] berichteten Upadhyaya et al kürzlich über verbesserte Konstrukte mit hoher Zellgängigkeit. [31,32] Aufbauend auf ihren früheren Arbeiten, in denen sie das effiziente Aufbrechen von Wechselwirkungen zwischen Ras und seinen Effektoren mithilfe kleiner Peptide demonstriert hatten, [32] berichteten Upadhyaya et al kürzlich über verbesserte Konstrukte mit hoher Zellgängigkeit.…”
Section: Cyclische Peptideunclassified
“…[31] Die erste ist ein Te il der Switch-Region Iu nd beinhaltet die Reste Asp33, Glu37 und Ser39; sie entspricht der Hauptbindungsstelle von 31MEW44 mit GemäßNMRspektroskopischen Studien stçrt Cyclorasin 9A5 zwei Gruppen geclusterter Reste.…”
Section: Niedermolekulare Verbindungenunclassified
See 1 more Smart Citation